Contribution of (sub)domains of Staphylococcus aureus fibronectin-binding protein to the proinflammatory and procoagulant response of human vascular endothelial cells - Heying, Ruth; Gevel, Joke van de; Que, Yok-Ai; Piroth, Lionel; Moreillon, Philippe; Beekhuizen, Henry (Thrombosis and Haemostasis, 2009)
The Staphylococcus aureus fibronectin (Fn) -binding protein A (FnBPA) is involved in bacterium-endothelium interactions which is one of the crucial events leading to infective endocarditis (IE). We previously showed that the sole expression of S. aureus FnBPA was sufficient to confer to non-invasive Lactococcus lactis bacteria the capacity to invade human endothelial cells (ECs) and to launch the typical endothelial proinflammatory and procoagulant responses that characterize IE. In the present study we further questioned whether these bacterium-EC interactions could be reproduced by single or combined FnBPA subdomains (A, B, C or D) using a large library of truncated FnBPA constructs expressed in L. lactis. Significant invasion of cultured ECs was found for L. lactis expressing the FnBPA subdomains CD (aa 604–877) or A4+16 (aa 432–559). Moreover, this correlates with the capacity of these fragments to elicit in vitro a marked increase in EC surface expression of both ICAM-1 and VCAM-1 and secretion of the CXCL8 chemokine and finally to induce a tissue factor-dependent endothelial coagulation response. We thus conclude that (sub)domains of the staphylococcal FnBPA molecule that express Fn-binding modules, alone or in combination, are sufficient to evoke an endothelial proinflammatory as well as a procoagulant response and thus account for IE severity.
Keywords: Bacterial infection; endothelial cells; inflammation; thrombosis; tissue factor / factor VII